2021
DOI: 10.1021/acscatal.1c01030
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Electrocatalysis by [Au25(SR)18]: Charge, Doping, and Ligand Removal Effect

Abstract: Considering the promising prospects of Au25(SR)18 q and its alloy clusters in numerous fundamental catalysis research studies derived from their well-defined structures, developing a deep understanding of the structure–property correlation becomes significantly urgent. Herein, we explored a prototype [Au25(SR)18] q cluster, monoatom-doped bimetallic [MAu24(SR)18] q clusters (M = Pt, Pd, Ag, Cu, Hg, or Cd), and their singly deligated M-exposure and S-exposure systems as electrocatalysts toward O2 reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…It is found that Pt(111) tends to follow the 4e − pathway, and the calculated limiting potential in our case is 0.66 eV, which slightly deviates by about 0.13 V compared to the previously reported value (0.79 eV). Note that herein only 27 MA 2 Z 4 with U L less than 1.23 V are displayed (Figure 4a S3, while the optimal ΔG OOH* should be around 3.69 eV), 62 111) catalyst (U L = 0.79 V), indicating its promising applications as a highly efficient ORR electrocatalyst. We further examined the ORR performance of the most promising CrGe 2 As 4 catalyst both with and without dispersion correction.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…It is found that Pt(111) tends to follow the 4e − pathway, and the calculated limiting potential in our case is 0.66 eV, which slightly deviates by about 0.13 V compared to the previously reported value (0.79 eV). Note that herein only 27 MA 2 Z 4 with U L less than 1.23 V are displayed (Figure 4a S3, while the optimal ΔG OOH* should be around 3.69 eV), 62 111) catalyst (U L = 0.79 V), indicating its promising applications as a highly efficient ORR electrocatalyst. We further examined the ORR performance of the most promising CrGe 2 As 4 catalyst both with and without dispersion correction.…”
Section: Resultsmentioning
confidence: 97%
“…Analysis of the O* adsorption strength (Table S4) revealed that they all exhibit very strong O* binding (0.81 eV for MoSi 2 P 4 , 0.90 V for WSi 2 P 4 , and 0.71 eV for WGe 2 P 4 , vs the optimal ΔG O* of 2.46 eV). 62 Such a high overpotential and ORR activity. The active sites of the screened catalysts are all located at the surface As atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, the well-defined NCs with resolved atomic structures are ideal model catalysts not only for the experimental probing of the key factors but also for computational modeling, thus providing opportunities for deeper mechanistic insight . Recently, Sun et al predicted the doping effects on the ORR based on gold NCs through theoretical simulations, indicating that the doping may significantly change the reaction mechanism of the ORR . However, direct experimental evidence of doping effects in atomically precise metal NCs is yet to be found, which will also provide opportunities for understanding more fundamental aspects.…”
Section: Introductionmentioning
confidence: 99%